Identification of inelastic parameters of the AISI 304 stainless steel: a multi-test optimization strategy - Vaz M.* (2020)
© 2020 Informa UK Limited, trading as Taylor & Francis Group.The AISI 304 stainless steel has largely been used in industry owing to its good formability characteristics. Therefore, the use of proper material parameters is essential for a successful numerical simulation of forming operations. Within this framework, this work addresses a parameter identification strategy using strategies based on multiple mechanical tests–a multi-test optimization scheme. The technique is used to determine isotropic hardening parameters of the AISI 304 steel using tensile tests of specimens of different geometries. The proposed method makes possible to obtain a representative set of material parameters taking into account the material response up to macroscopic failure. The study shows that the technique provides a minimum improvement of 30.43% in the global error function when comparing against single test results.